2013
DOI: 10.1016/j.virol.2012.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Canine distemper virus with the intact C protein has the potential to replicate in human epithelial cells by using human nectin4 as a receptor

Abstract: Recent outbreaks in monkeys have proven that canine distemper virus (CDV) causes diseases in a wide range of mammals. CDV uses SLAM and nectin4 as receptors to replicate in susceptible animals. Here, we show that human nectin4, but not human SLAM, is fully functional as a CDV receptor. The CDV Ac96I strain hardly replicated in nectin4-expressing human epithelial NCI-H358 cells, but readily adapted to grow in them. Unsurprisingly, no amino acid change in the H protein was required for the adaptation. The origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 44 publications
3
44
0
Order By: Relevance
“…In addition, our recent study suggested that CDV has the potential to counteract the human interferon system and replicate in human cells (12). Accordingly, CDV should be seriously considered a potential threat for humans.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, our recent study suggested that CDV has the potential to counteract the human interferon system and replicate in human cells (12). Accordingly, CDV should be seriously considered a potential threat for humans.…”
Section: Figmentioning
confidence: 99%
“…In part, this receptor specificity generates a species barrier for morbilliviruses. On the other hand, nectin-4, another morbillivirus receptor (8)(9)(10), is highly conserved in its amino acid sequence among different mammals and, thus, may play only a minor role in determining the host specificity of morbilliviruses (11,12). Recently, however, CDV outbreaks have emerged in a variety of mammals, including nonhuman primates, and showed high mortality rates (11,(13)(14)(15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Amino acid sequences for SLAM are variable among host species, and some key residues are important for virus binding (Ohno et al 2003). In contrast, nectin-4 is highly conserved among mammals, and no specificity has been reported among morbilliviruses (Otsuki et al 2013). Thus, SLAM is more likely than nectin-4 to play a crucial role in determination of host-virus specificity.…”
Section: Introductionmentioning
confidence: 99%
“…We found that MDCK cells were to some extent susceptible to the IC323 strain infection, as observed from the infection with the laboratoryadapted Edmonston strain (6). Using Vero cells expressing canine and human nectin4 (33,34), we found that canine nectin4 functions as an MV receptor as well as human nectin4 (data not shown). It was recently reported that MDCK cells express canine nectin4 (35).…”
Section: Resultsmentioning
confidence: 95%